To assess students’ perception about Kahoot! as an innovative learning tool in oral pathology- a qualitative study - , Mehwish Feroz Ali; Gulrukh Askary; Hasan Mehdi; Aiman Khan; Hibba Kaukab; Rida Qamar (Journal of the Pakistan Medical Association, 2021)
Objective: In the study, we investigated the perception of third profession dental students’ about Kahoot, as an innovative teaching, learning and assessment tool for the subject of Oral Pathology. Methods: A cross-sectional study carried out for the third professional dental students of Fatima Jinnah Dental College, Karachi, Pakistan. Kahoot app was implemented as a teaching and assessment tool in both first and second semester of the academic year 2019.Total 75 third year students enrolled in which 50 females and 25 males, age ranges from 20 to 22 years. At the end of the academic year, students’ opinion about Kahoot was assessed using a questionnaire-based analysis with a 5-point Likert-type scale. The questionnaire consisted of fifteen closed ended questions. The purposive non-probability sampling was selected to recruit students. Results: Around 90% (n=68) students agreed that kahoot-based learning facilitated them to comprehend and recall their knowledge of the topic and afterward discussion enhances further understanding. It stimulates a notion of self-directed learning among students n=69 (92%) to secure positions in the game which ensures learning satisfaction (94%) and make learning enjoyable. Continuous assessment tests result improved gradually with significant p-value <0.05. Continuous...